Pengaruh Media Wordwall terhadap Pemahaman Konsep Materi Ciri Khusus Hewan Peserta Didik Kelas IV Sekolah Dasar - Herlin Samrotul Yunaeni; Dya Ayu Agustiana Putri; Leny Suryaning Astutik (Universitas Nusantara PGRI Kediri, 2025)
Wordwall learning media can help teachers convey material, so that the material can be conveyed well which has an impact on students' understanding. The aim of the research is to determine the effect of wordwall media on the understanding of the concept of special characteristics of animals in class IV elementary school students. This research is quantitative with an experimental type. The sampling technique used saturated sampling for 56 respondents. The data collection technique uses a concept understanding test. The data analysis technique uses the t test (Independent Samples T-Test) in Jamovi 2.3.28. The results of the post-test t test showed that the p-value was <0.001, then the p-value was <0.05 and H0 was rejected and Ha was accepted, which means that there was an influence of wordwall media on the understanding of the concept of special characteristics of animals in class IV elementary school students. Based on the results of the hypothesis, it was found that there was a significant influence of wordwall media on the understanding of the concept of special characteristics of animals in class IV elementary school students.